OBJECTIVE EXAMINATIONS IN ELEMENTARY ACCOUNTING. - Dein, R. C. (The Accounting Review, 1942)
Abstract Objective examinations in accounting are a subject on which a good many people seem to have very definite and adverse, opinions. Perhaps the objective examination is usually thought of as consisting of a more or less formal list of true-or-false questions; and when the material of an accounting course does not seem to be particularly well adapted to this type of question, the conclusion is easily reached that the objective examination has little place in accounting. The object of this paper is, among other things, to suggest some of the possible forms that the objective examination in accounting may take in order to cure the difficulties of the true-or-false question. It may be that with adequate variety in the testing devices the objective examination may appear feasible as a testing device, if not positively desirable. An objective test in accounting has been defined as a test designed to cover a large amount of material, to have a large number of questions requiring very brief answers, the answers to each unit being the same for every student who answers the questions correctly.